A Rare Cause of Prolonged Fever and Cervical Lymphadenopathy: Kikuchi Fujimoto Disease - Mustafa Safa Tural; Sevliya Öcal Demir; Aylin Canbolat Ayhan; Bengü Çobanoğlu Şimşek (Çocuk Dergisi)
Kikuchi Fujimato Disease (KFD) is a rare and benign cause of cervical lymphadenopathy associated with fever. It is important to be aware of this disease as it is included in the differential diagnosis of diseases with high morbidity and mortality, such as lymphoma and tuberculosis. This study presents a child diagnosed with KFD to raise awareness of the disease. A 15-year-old female patient was admitted with neck swelling, weight loss, and fever for three weeks without response to antibiotic treatment. On examination, her temperature was 38oC, she had 3-4 fixed, painful, and hard cervical lymph nodes in cervical chains, the spleen was palpable at 1.5 cm, the liver at 1 cm, and other systems examination was normal. Laboratory tests revealed a neutrophil count of 770/L, lymphocyte of 800/L, C-reactive protein of 16.99 mg/L, and erythrocyte sedimentation rate (ESR) of 120 mm/h. Her fever and fatigue persisted during hospitalization, and no tests reveals infectious diseases. Peripheral blood smears, bone marrow aspiration microscopy, and flow cytometry did not reveal any findings in favor of malignancy, and excisional lymph node biopsy was performed for diagnosis. Histopathological examination was consistent with Kikuchi Fujimoto Disease. Antinuclear antibody (ANA) positivity (+++). The patient’s fever and partial lymphadenopathy resolved after 14 days of hospitalization, and the ESR decreased to 40 mm/h at 4 months. Systemic lupus erythematous (SLE) and hemophagocytosis can complicated KFD, so the follow-up patient continues. It is difficult to distinguish KFD from serious diseases clinically and in the laboratory. Differential diagnosis through histopathological evaluation is associated with the awareness of the clinician and the experience of the pathologist. With an early diagnosis, unnecessary examinations and treatments can be prevented.